Technology and education issues in administration, policy, and applications in K12 schools - Tettegah, Sharon Y.; Hunter, Richard C., Dr. (Amsterdam ; Oxford : Elsevier JAI, 2006)
In today's society where most students own MP3 players, engage in constant instant messaging and downloading from the Internet, more than ever school administrators and staff should be aware of issues in administration, policy, and applications. This book provides a comprehensive presentation of current policies and practices of technology in K12 schools. The first part of the book lays out the foundation of what schools should be concerned about involving various aspects of technology and its impact on school administration and teaching. The second part of the book introduces technology, policy and philosophical discussions on the use of technology in schools. The third section of the book provides an examination of technology of practical applications of technology currently used in schools. Sharon Tettegah holds faculty appointments in the Department of Curriculum and Instruction and Educational Psychology. She also has appointments with the National Center for Supercomputing Applications and the Beckman Institute at the University of Illinois, Urbana Champaign. Richard C. Hunter is a faculty member, and former chair in the Department of Educational Organization and Leadership in the College of Education at the University of Illinois, Urbana Champaign.
Foreword: rethinking educational technologies as architecture and aesthetics / Cushla Kapitzke -- Introduction / Sharon Tettegah -- Changing schools with technology: what every school should know about innovation / David M. Marcovitz -- Cyber-bullying and schools in an electronic era / Sharon Y. Tettegah, Diana Betout, Kona Renee Taylor -- Critical support framework for K-12 school and university technology partnerships / Lisa C. Yamagata-Lynch, Sharon Smaldino -- The pasteurization of education / David Williamson Shaffer, Kurt D. Squire -- Teacher as brand: pursuing professional identities in a digital domain / John B. Keller, Matthew J. Stuve -- Copyright, technology, and your rights / David M. Marcovitz -- Beyond the digital divide / Nicholas C. Burbules, Thomas A. Callister, Claudine Taaffe -- Technology and urban youth: emergent issues regarding access / Dawn G. Williams, Tawana L. Carr, Nicole S. Clifton -- Acceptable use policies in school districts: myth or reality? / Kona Renee Taylor, Eun Won Whang, Sharon Y. Tettegah -- Knowing and getting what you pay for: administration, technology, and accountability in K-12 schools / Saran Donahoo, Michael Whitney -- A hermeneutic approach towards integrating technology into schools: policy and practice / Mustafa Yunus Eryaman -- Educational digital libraries: platforms for innovation and equity / Marcia A. Mardis, Ellen S. Hoffman -- Integrating squeak into a community: a collaborative effort / Barbara Hug, George Reese -- Collaborative learning environments: developing SMART classrooms in theory and in practice / Bryan Carter, Tim Linder -- Can we talk? communication technologies, social informatics, and systemic change / Barbara Monroe -- Ubiquitous computing: rethinking teaching, learning, and technology integration / Karen Swan, Dale Cook, Annette Kratcoski, Yi Mei Lin, Jason Schenker, Mark van 't Hooft -- Digital photo journals: a novel approach to addressing early childhood technology standards and recommendations / Cynthia Carter Ching, X. Christine Wang, Yore Kedem -- Personal, professional, technical, and institutional factors involved in developing a computer-intensive english curriculum / Judith A. Federmeier, Renee T. Clift -- Superintendent leadership for technology integration in public education / Richard C. Hunter.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Educational technology -- United States; School management and organization -- United States; Teacher effectiveness -- United States; Educational technology -- Law and legislation -- United States; Organization & management of education; Education -- Computers & Technology